Managing Cracked Teeth with Root Extension: A Prospective Preliminary Study Using Biodentine™ Material - Kênia Maria Soares de Toubes; Isabella Sousa Corrêa; Regina Célia Lopes Valadares; Stephanie Quadros Tonelli; Fábio Fernandes Borém Bruzinga; Frank Ferreira Silveira (International Journal of Dentistry)
Purpose. The authors of this study proposed an innovative approach involving the use of Biodentine™ material as an intraorifice barrier in cracked teeth with root extension to promote internal crack sealing, preventing the possibility of microinfiltration and apical crack propagation. Materials and Methods. The dental records of 11 patients with 12 posterior cracked teeth with root extension were included with a precise protocol performed by a senior endodontist. The treatment protocol included pulp diagnosis, crack identification using a dental operating microscope (DOM), endodontic treatment, placing a Biodentine™ as an intraorifice barrier, and immediate full-coverage restoration. The effectiveness of the treatment was assessed at two intervals, 6 months, and 1−3 years posttreatment, evaluating clinical, radiographic, and tomographic aspects. The treatment was deemed successful if there were no indications of radiolucency, sinus tracts, edema, or periodontal pockets associated with the crack line. Results. The study observed remarkably positive outcomes during the follow-up period, which spanned from 1 to 3 years. All the cracked teeth (100%) remained asymptomatic, meaning they were free of pain or discomfort. Furthermore, these teeth were in occlusal function. Both radiographic and tomographic assessments revealed the absence of bone loss along the crack line. This outcome signifies that the treatment effectively prevented further deterioration of the surrounding bone. Conclusions. Integrating advanced biomaterials and conservative restorative techniques has paved the way for innovative approaches in dental care. This protocol suggests a proactive step for managing cracked teeth with root extension. It addresses both biological aspects by sealing internal cracks and mechanical aspects by preventing crack progression, thereby improving these teeth’ prognosis and long-term survival.